The Role of Husband Support in the Success of Exclusive Breastfeeding Literature Review - Megawati Megawati; Aura Anzila; Intan Kumala Dewi (Journal of Innovative and Creativity, 2026)
The study purpose was to examine the role of husband support in the success of exclusive breastfeeding among mothers of infants aged 0–6 months. Despite strong recommendations by the World Health Organization (WHO) for exclusive breastfeeding during the first six months of life, global and national coverage—particularly in Indonesia—remains below target. Among various determinants, husband support has emerged as a significant psychosocial and environmental factor influencing breastfeeding practices. This literature review synthesizes empirical findings from 25 peer-reviewed studies published between 2015 and 2025, aiming to identify the forms of husband support most strongly associated with exclusive breastfeeding success and to analyze the theoretical frameworks that explain this relationship. Materials and methods. A systematic literature review was conducted following PRISMA guidelines. Databases including PubMed, Scopus, ScienceDirect, Google Scholar, and Garuda were searched using keywords such as husband support, exclusive breastfeeding, and breastfeeding self-efficacy. Studies were included if they examined husband involvement in exclusive breastfeeding and were published in English or Bahasa Indonesia within the last decade. Results. The findings revealed that emotional and instrumental support were the most influential factors in maintaining exclusive breastfeeding, while informational and appraisal support enhanced maternal confidence and motivation. Husband participation in antenatal education and shared household responsibilities significantly increased breastfeeding duration and exclusivity rates. Conclusions. Husband support plays a pivotal role in promoting and sustaining exclusive breastfeeding. Integrating men into family-centered breastfeeding education and policy interventions is essential to improve maternal and infant health outcomes.